In situ analysis of the forging process of a novel γ‐TiAl alloy using synchrotron radiation: In situ Untersuchung des Schmiedeprozesses einer neuartigen γ‐TiAl Legierung unter Verwendung von Synchrotronstrahlung. Issue 11 (16th November 2016) - Tankoua, A. Tchouaha; Stark, A.; Rackel, M. W.; Pyczak, F.; von Hehl, A.
Abstract : Because of their good properties, the γ‐TiAl based alloys are promising to replace the twice as dense yet established nickel‐based alloys e.g. in turbine blades and especially low pressure turbine blades in aircraft engines. The serial production of such parts made of the γ‐TiAl based alloys requires the development of a stable processing route. However, during forging, the starting material's properties undergo many modifications at elevated temperature. Therefore, it is important to understand which changes in microstructure, phase constitution and texture appear during processing at high temperatures. With conventional metallographic methods, the study of these effects can only be achieved after processing. X‐ray diffraction with synchrotron radiation is a special analysis method that allows in situ and time resolved studies of the changing properties during the thermo‐mechanical treatment. In this study, experiments have been performed during forging, in temperature ranges of 1100 °C to 1300 °C, with different deformation rates between 0.002 and 0.03 s –1 . The results of these experiments provide a basis for a process window for the serial production of forged parts made of the intermetallic alloy Ti–42Al–8.5Nb (in at%).